Large-scale assessment of myxomatosis prevalence in European wild rabbits (Oryctolagus cuniculus) 60 years after first outbreak in Spain. (October 2017) - Villafuerte, Rafael; Castro, Francisca; Ramírez, Esther; Cotilla, Irene; Parra, Francisco; Delibes-Mateos, Miguel; Recuerda, Pilar; Rouco, Carlos
Abstract: Myxomatosis is a viral disease that affects European rabbits ( Oryctolagus cuniculus ) worldwide. In Spain, populations of wild rabbits drastically decreased in the 1950s after the first outbreak of myxomatosis. Since that first appearance, it seems to be an annual epizootic in Spain with periodic outbreaks, predominantly in summer and autumn. Taking into account rabbit population structure, abundance, and genetic lineage, this paper attempts to make a large-scale characterization of myxomatosis seroprevalence based on the immune status of 29 rabbit populations distributed throughout Spain, where O . cuniculus cuniculus and O . c . algirus, the two known rabbit subspecies, naturally inhabit. A total of 654 samples were collected between 2003 and 2009, and seroprevalence of antibodies against Myxoma virus (MYXV) was determined. Overall, our results revealed that 53% of the rabbit samples were positive to antibodies against MYXV. Newborn and juvenile rabbits were the most susceptible animals to the virus, with 19% and 16% seropositivity for newborn and juveniles, respectively, while adult rabbits were the most protected, with 65% of seropositive samples. This suggests that prevalence is negatively related to the proportion of newborn and juvenile rabbits in a population. Our results also showed that seroprevalence against MYXV tended to be higher in high-abundance populations. In contrast, no differences were detected in seroprevalence between rabbit subspecies. This study confirms that > 60 years since first outbreak, myxomatosis is an endemic disease in Spain. Based on the results, the establishment of a myxomatosis surveillance protocol is proposed. Highlights: Myxomatosis is a viral disease that affects European rabbits worldwide We characterize the seroprevalence of myxomatosis in Spain at a nationwide scale We assessed how age, subspecies, ecological, biological or methodological variables influence the immune status of wild populations Seroprevalence against Myxoma virus tended to be higher in high-abundance populations There is a need for establishment of a myxomatosis surveillance protocol.